2021
DOI: 10.1088/1402-4896/ac267b
|View full text |Cite
|
Sign up to set email alerts
|

D retention and material defects probed using Raman microscopy in JET limiter samples and beryllium-based synthesized samples

Abstract: We report on the detection by means of Raman spectroscopy of amorphous beryllium deuteride, BeD2, in magnetron sputtered deposits synthesized in two different laboratories and containing about 20 at% of deuterium. In contrast, this signature has not been found for the JET limiter samples studied coming from the inner, outer or upper limiters, even when coming from a deposition zone of the limiters. We give a way to disentangle that BeD2 signature from other signatures falling in the same spectroscopic range an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Using magnetron sputtering, and creating samples with a D content as high as 20 at.%, we have found that a broad signature could lie close to 1000 cm −1 , in agreement with previous references plus a narrower band close to 1200 cm −1 [68]. These two bands have been seen only on a very limited number of samples [68]. We believe that this is due to four reasons: (1) they fall at the same position as the intense 2PDOS signature.…”
Section: Raman Spectroscopy Of Beryllium Carbides Hydrides and Oxidessupporting
confidence: 92%
See 4 more Smart Citations
“…Using magnetron sputtering, and creating samples with a D content as high as 20 at.%, we have found that a broad signature could lie close to 1000 cm −1 , in agreement with previous references plus a narrower band close to 1200 cm −1 [68]. These two bands have been seen only on a very limited number of samples [68]. We believe that this is due to four reasons: (1) they fall at the same position as the intense 2PDOS signature.…”
Section: Raman Spectroscopy Of Beryllium Carbides Hydrides and Oxidessupporting
confidence: 92%
“…This is, unfortunately, in the range where the 2PDOS lies. Using magnetron sputtering, and creating samples with a D content as high as 20 at.%, we have found that a broad signature could lie close to 1000 cm −1 , in agreement with previous references plus a narrower band close to 1200 cm −1 [68]. These two bands have been seen only on a very limited number of samples [68].…”
Section: Raman Spectroscopy Of Beryllium Carbides Hydrides and Oxidessupporting
confidence: 91%
See 3 more Smart Citations